Recognising Familiar Faces Out of Context. (February 2021) - Laurence, Sarah; Eyre, Jordyn; Strathie, Ailsa
Expertise in familiar face recognition has been well-documented in several studies. Here, we examined the role of context using a surprise lecturer recognition test. Across two experiments, we found few students recognised their lecturer when they were unexpected, but accuracy was higher when the lecturer was preceded by a prompt. Our findings suggest that familiar face recognition can be poor in unexpected contexts.